Passing the Torch - Corbett, Glenn J. (The Biblical archaeology review, 2022)
BAR has witnessed several important transitions over the past few years, and this issue marks yet another. Susan (Sue) Laden, the magazine’s longtime Publisher and the guiding force behind the Biblical Archaeology Society (BAS), is stepping back after nearly five decades of service to the organization (see "Celebrating BAR Publisher Susan Laden"). Her role […]